Assessment of Likelihood Ratio of the Medicines Enlisted under the Rubric “Pain, Knee, Motion, Amelioration” in the Extremities Chapter of Kent's Repertory - Roy, Urmi; Pal, Rajat K.; Saha, Subhranil; Alam, Sk Monsur; Koley, Munmun; Gole, Raghubir; Sengupta, Sumana; Sultana, Quamar; Nag, Usashi; Koley, Mousumi; Hashmi, Shifa; Midya, Ayan; Chakraborty, Doly; Biswas, Swarup; Ganguly, Subhasish; Rutten, Lex (Homeopathy, 2025)
Background “Pain, Knee, Motion, Amelioration” in the Extremities chapter of Kent's repertory with 20 enlisted medicines is one of the most frequently encountered rubrics in homeopathy but has not been evaluated systematically. Bayesian statistics resulting in the likelihood ratio (LR) could offer a better evaluation of the enlisted medicines as well as the eligibility of other medicines.Methods An analytical, epidemiological, longitudinal outcome study was conducted in different outpatient departments of D.N. De Homoeopathic Medical College and Hospital, Kolkata, on 1,204 patients over 18 months using ORIDL (Outcome Related to Impact on Daily Living), whose scale ranges from +4 to −4. Results were documented during each follow-up, continuing until the most recent visit at an average of 3 months. The LRs were reported with their corresponding 95% confidence intervals (CIs).Results Analysis included 1,204 cases with 20 enlisted medicines and 37 not enlisted homeopathic medicines. The prevalence of the rubric “Pain, Knee, Motion, Amelioration” was 18.8%. Among the enlisted ones, the medicines having LR ≥ 1.5 were Calcarea carbonicum LR(+) 1.7 (95% CI: 0.8 to 3.5) and Rhus toxicodendron LR(+) 2.3 (95% CI: 1.7 to 3.1). Some medicines with LR ≥ 1.5 that were not previously enlisted in the rubric were Arnica montana LR(+) 2.0 (95% CI: 0.9 to 4.3), Carbo vegetabilis LR(+) 1.8 (95% CI: 0.8 to 4.0), and Staphysagria macrosperma LR(+) 1.5 (95% CI: 0.5 to 5.0). Overall, the findings corroborated the medicines' listing under the rubric in Kent's repertory.Conclusion There was substantial evidence to link some of the enlisted medicines with the said rubric. Additional research involving a larger population is needed to address the potential confirmation bias.
Keywords: Bayesian statistics; homeopathy; likelihood ratio; Kent's repertory